Parameter Uji Yang Berhubungan Dengan Penerimaan Vaksin Covid-19 Pada Masyarakat di Kecamatan Jangka Kabupaten Bireuen Tahun 2022 - Mirai, Kirana Ulil; Maksum, Rianada; Karim, Fatahul (Media of Health Research, 2024)
Covid-19 Vaccination as a government policy program worldwide aims to reduce Covid-19 transmission, lower morbidity and mortality rates due to Covid-19, achieve herd immunity in society, and protect the public from Covid-19 so that they remain socially and economically productive. The purpose of this study is to identify the factors related to Covid-19 vaccine acceptance among the community in Jangka Subdistrict. This study was conducted using a quantitative method with a cross-sectional approach. The population in this study consisted of 364 individuals from Jangka Subdistrict. A sample of 85 respondents was selected using random sampling, specifically the simple random sampling technique, with the Slovin formula used to determine the sample size. Data collection was carried out over 10 days. Data analysis employed both univariate and bivariate methods using the chi-square test. The results of the study, based on univariate analysis, show that out of the 85 respondents, 36 respondents (42.4%) had received the full Covid-19 vaccine, while 49 respondents (57.6%) had not received the full Covid-19 vaccine. Variables related to Covid-19 vaccine acceptance include knowledge, attitude, occupation, and stigma (P=0.000). However, variables that were not related include gender (P=0.967), information sources (P=0.154), and comorbidities (P=0.996).